1987
DOI: 10.1002/aic.690331214
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to study gas phase reactions

Abstract: To understand better the impact of gas phase reactions on chemical vapor deposition, a new experimental method has been developed to isolate and study homogeneous reactions separately from heterogeneous reactions. This new system heats reactant gases by rapidly compressing them to temperatures greater than 1,000 K; the walls of the reactor remain constant at 500 K or less. Pressure and volume measurements determine the mean temperature of the gas. Results from a series of test reactions and simple models show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Note that the peak T,,, is roughly the same in both experiments. Morrison and Reimer (1987) have shown that the sharpness of the peak T, is largely due to the rebound of the piston (expansion cooling). Figure 3 shows the conversion as a function of peak T,,, for 1% mixtures of SiH, in Ar and He.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that the peak T,,, is roughly the same in both experiments. Morrison and Reimer (1987) have shown that the sharpness of the peak T, is largely due to the rebound of the piston (expansion cooling). Figure 3 shows the conversion as a function of peak T,,, for 1% mixtures of SiH, in Ar and He.…”
Section: Resultsmentioning
confidence: 99%
“…A previous manuscript describes the reactor in detail (Morrison and Reimer, 1987), and we only review the principles here ( inside diameter of 10 cm; a substrate or window closes one end of the cylinder. A piston and rod assembly slides inside the cylinder forming a gas tight seal; a Teflon coating on the interior cylinder surface lubricates the piston seals.…”
Section: Experimental Descriptionmentioning
confidence: 99%
See 2 more Smart Citations